Water- and Base-Extractable Organic Matter in Sediments From Lower Yangtze River–Estuary–East China Sea Continuum: Insight Into Accumulation of Organic Carbon in the River-Dominated Margin - Han, Lulu; Wang, Yinghui; Xu, Yunping; Wang, Yasong; Zheng, Yiling; Wu, Jianqiang (Frontiers in Marine Science, 2021)
The burial of organic carbon (OC) in the river-dominated margin plays an important role in global carbon cycle, but its accumulation mechanism is not well understood. Here, we examined the concentration and distribution of water-extractable organic matter (WEOM) and base-extractable organic matter (BEOM) in surface sediments from the lower Yangtze River, estuary, and the East China Sea. Chemical characteristics of the WEOM and BEOM were described by multiple ultraviolet-visible and fluorescence spectral indicators. Concentrations of both WEOM and BEOM showed significant correlations with sediment grain size, suggesting that mineral surface area is a key factor for OC loadings on sediments. Three components (C1, C2, and C3) extracted from fluorescence excitation emission matrices-parallel factor analysis were assigned as terrigenous humic-like substance, mixed terrigenous/aquatic humic-like substance, and microbial protein-like substance, respectively. From the lower Yangtze River to the East China Sea, the C1%, specific UV absorbance at 254 nm (SUVA254), and humification index (HIX) of the WEOM decreased, while the C3%, fluorescence index (FI), and biological index (BIX) of the WEOM increased. This suggested the loss of terrigenous OC and addition of microbial OC in the WEOM. While for BEOM, the overall increase of C1% and HIX and the decrease of C3% and FI suggested selective removal of microbial OC and preferential preservation of terrigenous OC. Our study demonstrates complex behaviors of sediment organic matter (OM) during the land-to-sea transport that is largely controlled by the binding strength of OM–sediment association, and that the formation of BEOM is an important pathway for accumulation of terrigenous OM in the river-dominated margin.